A review on the pollution assessment of hazardous materials and the resultant biorefinery products in Palm oil mill effluent. (1st July 2023) - Meena R, Anu Alias; J, Merrylin; Banu J, Rajesh; Bhatia, Shashi Kant; Kumar, Vinod; Piechota, Grzegorz; Kumar, Gopalakrishnan
Abstract: The voluminous nature of palm oil mill effluent (POME) is directly associated with environmental hazards and could be turned into biorefinery products. The POME, rich in BOD, COD, and oil and grease, with few hazardous materials such as siloxanes, fatty acid methyl ester, and phenolic compounds that may significantly increase the risk of violating the effluent quality standards. Recently, the application of chemical and biological risk assessment that can use electrochemical sensors and microalgae-like species has gained paramount attention towards its remediation. This review describes the existing risk assessment for POME and recommends a novel assessment approach using fish species including invasive ones as suitable for identifying the toxicants. Various physico-chemical and biological treatments such as adsorption, coagulation-flocculation, photo-oxidation, solar-assisted extraction, anaerobic digestion, integrated anaerobic-aerobic, and microalgae cultivation has been investigated. This paper offers an overview of anaerobic technologies, with particular emphasis on advanced bioreactors and their prospects for industrial-level applications. To illustrate, palmitic acid and oleic acid, the precursors of fatty acid methyl ester found in POME pave the way to produce biodiesel with 91.45%. Although there are some challenges in attaining production at an economic scale, this review offers some opportunities that could help in overcoming these challenges. Graphical abstract: Image 1 Highlights: This review emphases on POME biorefinery and its environmental hazards. Various treatment options of POME treatment and biorefinery schemes were discussed. Different pollution assessment methods were highlighted. Biological risk assessment with possible remediations was elaborated.